Patisson (Cucurbita Pepo.Var.Melopepo) Plant Cultivation Technology and Consumption Methods - Rahmonovna, Kenjayeva Tolganoy; Jorayevich, Nurmatov Norkobil; Marjona, Khushbakova (European Journal of Life Safety and Stability (2660-9630), 2023)
Patisson is a highly intensive crop that can be grown in open and sheltered areas. In Uzbekistan, very little research has been conducted on the patisson (kulcha pumpkin) crop. 2 varieties of Patisson are included in the State Register. Zarkokil and Ak-13 varieties.